Perbedaan Pengaruh Latihan Crossover-Drive Jump Shoot Dengan Latihan Step-Back Jump Shoot Terhadap Hasil Jump Shoot Pada Permainan Bolabasket Siswa Putra Ekstrakurikuler SMA Negeri 2 Binjai - Ferzia Bima Rianza Nasution; Andi Nur Abady; Albert Ronaldo Zendrato; Yosua Alberto Siahaan; Fajar Sidik Siregar; Alif Albukhori; Andi Suranta Bangun; Aldifta Fahluzi (PT Mediatama Zayna Indonesia, 2024)
Crossover-drive jump shoot drills and step-back jump shoot drills are two drills that can improve jump shoot results in basketball games. A basketball player must have a good and correct jump shoot in order to get maximum results. This research aims to determine basketball training considering that the greater influence is between crossover-drive jump shoot training or step-back jump shoot training on jump shoot results in extracurricular basketball games for male students at SMA Negeri 2 Binjai in 2024. The research method used in this research is an experimental method and implementation of training, namely crossover-drive jump shoot training and step-back jump shoot training. The population in this study was 12 basketball extracurricular male students in 2024. The total sample was 12 people using a total sampling technique, then divided into two groups using the match by pairing technique, namely crossover-drive jump shoot training with step-back jump shoot training. The research instrument for collecting data using tests and measurements is the jump shoot test. The research was carried out for 6 (six) weeks with training 3 (three) times a week. To see the influence of each independent variable and the limitations, statistical calculations of the crossover-drive jump shoot t-test and the step-back jump shoot t-test were used. Hypothesis testing: (1) Hypothesis I analysis of the increase in jump shoot results for the crossover-drive jump shoot training group obtained t of 11.7 and t of 2.571 with α = 0.05 (t > t) meaning that Ho was rejected and Ha was accepted. (2) Hypothesis II analysis of the increase in jump shoot results in the step-back jump shoot training group obtained t of 6.26 and t of 2.571 with α = 0.05 (t > t ) meaning that Ho was rejected and Ha was accepted. (3) Analysis of hypothesis III from the average and standard deviation obtained t 1.96 and t 2.228 with α = 0.05 (t < t ) meaning Ho is accepted and Ha is rejected. Research conclusions: (1) There is a significant influence of crossover-drive jump shoot training on jump shoot results in extracurricular basketball games for male students at SMA Negeri 2 Binjai in 2024. (2) There is a significant influence of step-back jump shoot training on results of jump shoots in extracurricular boys' basketball games at SMA Negeri 2 Binjai in 2024. (3) Crossover-drive jump shoot training has no greater influence than step-back jump shoots on jump shoot results in extracurricular boys' basketball games in high schools Negeri 2 Binjai in 2024.